Ocorrência de moscas brancas (Hemiptera: Aleyrodidae) e do predador Delphastus pusillus (LeConte) (Coleoptera: Coccinellidae) em mamoeiro (Carica papaya L.) sob cultivo em ambiente protegido - Vieira, Marineide R. [UNESP]; Correa, Luiz S. [UNESP] (My University, 2001)
We report the presence of whitefly species at the Experimental Farm of UNESP, located in Selvíria, state of Mate Grosso do Sul, Brazil (20°22′ latitude S, 51°22′ longitude W, altitude 335 m), in February and October 1998. These insects were found on papaya trees cultivar Baixinho de Santa Amália, grown under screened conditions (2 mm × 2 mm mash). The goal of the original experiment was to determine the effect of growing the cultivar under a protected environment on the development of the trees, fruit production and incidence of the papaya ringspot virus. Whitefly specimens were sent to the Center of Genetic Resources and Biotechnology (CENARGEN) of EMBRAPA, for identification. The specimens collected in February were identified as Trialeurodes sp. and those collected in October were recognized as Bemisia tabaci biotype B. In both ocasions there were great numbers of nymphs on mature leaves and of adults on young leaves. We counted the number of Trialeurodes nymphs in eighteen leaves, in five areas of 1 cm 2 per leaf, distributed at random, where we found an average of 7.6 nymphs/cm2. The only damage associated with the presence of whitefly of both species was the intense development of 'sooty molds', covering completely the leaves, which wilted and fell. The infestation of B. tabaci biotype B was controlled by larvae and adults of the coccinellid Delphastus pusillus (LeConte), which fed avidly on the whitefly nymphs.
Whiteflies (Hemiptera: Aleyrodidae) and the predator Deiphastus pusillus (Le Conte) (Coleoptera: Coccinellidae) on papaya tree (Carica papaya L.) grown under screened conditions
Keywords: Bemisia tabaci biotype B; Insecta; Screened; Sooty molds; Trialeurodes